Reading and Studying on the Screen: An Overview of Literature Towards Good Learning Design Practice - Mark Nichols (Flexible Learning Association of New Zealand, 2016)
As distance education moves increasingly towards online provision, and because of the benefits provided by online approaches, students will be expected to engage with more resources available on screen. Contemporary forms of reading from the screen include reading from tablet devices, LCD monitors, and smartphones. However, print remains the preferred means of reading text, and student preference for print is accentuated when reading involves thorough study (Ackerman & Lauterman, 2012; Foasberg, 2014). Education providers face an interesting challenge. Although many learners prefer having access to printed materials, on-screen reading can improve education's convenience, portability, media-richness, engagement, support, and data-evidenced practice. In this context it is timely to consider the potential for on-screen reading from the perspective of learning design. This article considers studies related to reading on screen, and suggests good practice principles for on-screen-only learning design.